Implementation of Problem-Based Learning (PBL) Learning Model to Improve Learning Motivation of Class V Students - Sitepu, Juli Maini; Laedi, Siti Hajar; Azizah, Azizah; Asriani, Asriani; Sitepu, Melyani Sari (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to explore how the role playing learning model can improve students’ speaking skills in Indonesian language lessons at the Madrasah Ibtidaiyah (Islamic elementary school) level. Initial observations showed that many fourth-grade students lacked confidence when speaking in public. They often appeared awkward, hesitant, and were not actively engaged in the learning process.The study uses a quantitative approach with a pre-experimental design. Data were collected before and after the implementation of the role playing model to assess any changes in students’ speaking abilities. All 24 fourth-grade students at MIS Madinatussalam were involved as research participants.Data collection methods included direct speaking tests, documentation, and performance assessments based on specific speaking skill indicators. To analyze the results, an independent sample t-test was conducted using the SPSS software to determine whether there was a significant difference between the pre-test and post-test scores. The findings revealed that the role playing model had a positive effect on students' speaking skills. This was shown by an increase in the average score from 18.04 (pre-test) to 22.33 (post-test). The significance value of 0.00 indicates that the improvement is statistically significant.Based on these results, it can be concluded that the role playing learning model is effective in improving the speaking skills of fourth-grade students in Indonesian language instruction.